The effect of electronic word of mouth, brand image, and trust on purchase intention - Maulana, Nurul Shalsadila; Rahmiati (Marketing Management Studies, 2023)
This study aims to analyze the effect of Electronic Word of Mouth on Purchase Intention with Brand Image and Trust as Mediating Variables on Tiktok Users in Padang City. The population in this study were all people in Padang City who know the TikTok application. This study included 196 respondents as samples. Data was collected by distributing online questionnaires, and data was processed using SmartPLS software. The findings of this study show that (1) electronic word of mouth has a positive and significant effect on purchase intention, (2) electronic word of mouth has a positive and significant effect on brand image, (3) brand image has a positive and significant effect on purchase intention, (4) electronic word of mouth has a positive and significant effect on purchase intention mediating by brand image, (5) electronic word of mouth has a positive and significant effect on trust. (6) trust has a positive and significant effect on purchase intention, and (7) electronic word of mouth has a positive and significant effect on purchase intention mediating by trust.